Trends in the utilization of opioid analgesics in Malaysian healthcare facilities: a cross sectional observational study - Zin, Che Suraya (2016)
There is currently limited data available on the patterns of opioid prescribing in Malaysia. This study investigated the patterns of opioid prescribing and characterized the dosing and duration of opioid use. The co-prescription of opioid with benzodiazepine and other concomitant medications among opioid users was also examined. Methods This retrospective cross sectional study was conducted at an outpatient hospital setting in Malaysia. All prescriptions for opioids (dihydrocodeine, fentanyl, morphine and oxycodone) issued between January 2013 and December 2014 were included. The co-prescription of opioid with other medications (opiod+benzodiazepines, opioid+antidepressants, opioid+anticonvulsants, opioid+antipsychotics and opioid+hypnotics) among opioid users was also examined. The number of prescriptions and patients including the number of co-prescriptions, the distribution of mean daily dose and annual total days covered with opioids at the individual level were calculated and stratified by noncancer and cancer groups. Results A total of 1015 opioid prescriptions were prescribed for 347 patients from 2013 to 2014. Approximately 41.5% of patients (n=144/347) and 58.5% (n=203/347) were associated with noncancer and cancer diagnosis respectively. Oxycodone (38.0%) was the highest prescribed primarily for the noncancer group. Majority of patients in both noncancer (74.3%) and cancer (60.4%) groups were receiving mean daily doses of <50 mg morphine equivalents. The chronic use of opioid (>90 days per year) was associated with 21.8% of patients in the noncancer group and 17.5% in the cancer group. Among opioid user receiving concomitant medications, 12.3% of patients received co-prescriptions of opioid+benzodiazepine, 19.3% received opioid+anticonvulsant, 6.3% received opioid+antidepressant and 10.9% received other co-prescriptions including antipsychotics and hypnotics. Conclusions The finding from this study showed that 41.5% of opioid users at an outpatient hospital setting in Malaysia received opioids for noncancer pain and 21.8% of these users were using opioid for longer than 90 days. The average daily dose in majority of patients in both groups of noncancer and cancer is modest. Among the opioid users receiving concomitant medications, the co-prescriptions of opioid with benzodiazepine were prescribed to 12.3% patients. Future studies are warranted to evaluate details of opioid use and examine the clinical outcomes, relationship between socio-demographic, and medical and psychiatric factors in patients with long term opioid therapy for chronic noncancer pain particularly for those using the co-prescription.